Switching Response in Organic Electrochemical Transistors by Ionic Diffusion and Electronic Transport - Juan Bisquert; Baurzhan Ilyassov; Nir Tessler (Advanced Science)
Abstract The switching response in organic electrochemical transistors (OECT) is a basic effect in which a transient current occurs in response to a voltage perturbation. This phenomenon has an important impact on different aspects of the application of OECT, such as the equilibration times, the hysteresis dependence on scan rates, and the synaptic properties for neuromorphic applications. Here we establish a model that unites vertical ion diffusion and horizontal electronic transport for the analysis of the time‐dependent current response of OECTs. We use a combination of tools consisting of a physical analytical model; advanced 2D drift‐diffusion simulation; and the experimental measurement of a poly(3‐hexylthiophene) (P3HT) OECT. We show the reduction of the general model to simple time‐dependent equations for the average ionic/hole concentration inside the organic film, which produces a Bernards‐Malliaras conservation equation coupled with a diffusion equation. We provide a basic classification of the transient response to a voltage pulse, and the correspondent hysteresis effects of the transfer curves. The shape of transients is basically related to the main control phenomenon, either the vertical diffusion of ions during doping and dedoping, or the equilibration of electronic current along the channel length.